2020
DOI: 10.1017/s146342362000047x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of family physician residents of their roles in disaster health management: a cross-sectional study in Turkey

Abstract: Aim: Family physicians are role models for their societies in disaster management and have an important place in it. This study was carried out during the specialty training of the residents, who are currently family physicians fighting against COVID-19 in the field, and was aimed to identify the awareness levels of residents regarding the roles and duties of family physicians before, during, and after disasters and to increase their awareness of disaster medicine and management. Background: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Moreover, only 9.2% stated that they received training on disaster medicine where they work, the large majority (83.3%) had never joined a disaster drill, and the large majority (94.3%) had never participated in making a disaster plan. Also, the large majority had never worked in a disaster [2]. The findings of the Turkish study were poorer compared to our findings, and the participants in our study showed a higher level of knowledge, attitude and received more training.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Moreover, only 9.2% stated that they received training on disaster medicine where they work, the large majority (83.3%) had never joined a disaster drill, and the large majority (94.3%) had never participated in making a disaster plan. Also, the large majority had never worked in a disaster [2]. The findings of the Turkish study were poorer compared to our findings, and the participants in our study showed a higher level of knowledge, attitude and received more training.…”
Section: Discussioncontrasting
confidence: 99%
“…Family physicians had a pivotalrole in their responding to the medical community needs due to the natural and/or man-made disasters [1]. Family physicians had a crucial role in disaster health management [2] as when they know persons at risks before a disaster strikes, they form essential health forces in the disaster management and implement a risk health management on a regional scale [2]. Additionally, when the disasters strike, family physicians are being at the front lines in their communities' responses [1].During and after a disaster, family physicians take several tasks and duties, such as event detection, critical information' collection and distribution, intervention by triage, and rehabilitative activities [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations